A framework of heterogeneous cloud service and multi attributes negotiation using double auction - Adnan, M.H.M. (World Academy of Research in Science and Engineering, 2020)
Many double auction frameworks have been proposed for cloud service negotiations 1. However, the frameworks are not able to accommodate both the heterogeneous cloud services and multi-attributes negotiation simultaneously. Therefore, this paper proposed a double-auction framework to accommodate heterogeneous cloud services and multi-attributes negotiation. The study postulated four activities namely literature review, cloud service marketplace investigation, data formulation and double auction-based negotiation framework development. The market requirements, auction requirements and two new mechanisms of a double auction framework have been proposed. Â© 2020, World Academy of Research in Science and Engineering. All rights reserved.